2002
DOI: 10.1109/tmag.2002.801906
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic relaxations in metallic multilayers

Abstract: Abstract-The intrinsic damping mechanism in metals caused by incoherent scattering of itinerant electron-hole pair excitations by phonons and magnons will be reviewed. The unique features of magnetic relaxations in multilayers were studied by ferromagnetic resonance (FMR) using magnetic single, Au-Fe-GaAs(001), and double layer Au-Fe-Au-Fe-GaAs(001) structures prepared by molecular beam epitaxy. The magnetic relaxation in single-layer films is described by the Gilbert damping with no extrinsic contributions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…By using the same interaction potential it is shown 16,28 that the Gilbert damping from the dynamic interlayer exchange coupling, G sϪd , is similar to that using the spinpumping theory 8 combined with a perfect spin sink. This leads to an important conclusion: The spin pumping theory is equivalent to the dynamic response of the interlayer exchange coupling.…”
Section: Theoretical Models Of Nonlocal Dampingmentioning
confidence: 86%
See 2 more Smart Citations
“…By using the same interaction potential it is shown 16,28 that the Gilbert damping from the dynamic interlayer exchange coupling, G sϪd , is similar to that using the spinpumping theory 8 combined with a perfect spin sink. This leads to an important conclusion: The spin pumping theory is equivalent to the dynamic response of the interlayer exchange coupling.…”
Section: Theoretical Models Of Nonlocal Dampingmentioning
confidence: 86%
“…2,26,27 The in-plane ferromagnetic resonance ͑FMR͒ experiments were carried out using 10, 24, 36, and 72 GHz systems. 3 Single Fe ultrathin films with thicknesses of 8,11,16,21, and 31 monolayers ͑MLs͒ were grown directly on GaAs͑001͒.…”
Section: Nonlocal Damping Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal magnetic field is treated by employing Maxwell's equations. A precessing magnetization in FM creates a spin current which is described by spin pumping proposed by Tserkovnyak et In our recent ferromagnetic resonance ͑FMR͒ studies [1][2][3][4] it was shown that the transfer of the spin momentum across ferromagnetic ͑FM͒/normal metal ͑NM͒ interfaces can result in nonlocal interface Gilbert damping GЈ. The generation of spin momentum in magnetic ultrathin films was theoretically described by Tserkovnyak et al 5 and the effect was called ''spin pumping.''…”
mentioning
confidence: 99%
“…The presence of a second magnetic layer creates a spin sink. 3,4,6,7 The combination of spin pump and spin sink in the ballistic limit leads to an additional interface Gilbert damping. In this article we extend the spin pump and spin sink mechanisms to the nonballistic electron transport which includes a full treatment of the Landau-Lifshitz ͑LL͒ equation of motion in FM and diffusion equation in NM and Maxwell's equations accounting for a finite penetration of the rf fields.…”
mentioning
confidence: 99%